Modeling, Simulation and Monitoring of Electrical Contacts Temperature in Railway Electric Traction - Alin Dragomir; Maricel Adam; Mihai Andrusca; Gheorghe Grigoras; Marian Dragomir; Seeram Ramakrishna (Mathematics, 2021)
The paper presents a mathematical modeling approach to determine the permanent regime temperature of an electric contact found in the supply system of the railway electric traction. Mathematical modeling is a basic procedure in the preliminary determination of parameters of interest in various fields of scientific analysis. The numerical modeling method used for determining the electric contact temperature represents the base for developing a finite-element thermal model. The simulation of the electric contact was verified by an experimental infrared investigation of an electric contact realized on a realistic laboratory setup. The results interpretation reveals a good synchronization between the calculated, simulated and measured temperatures.